EVALUATION OF VALUE-ADDED TAX ON THE FULFILLMENT OF TAX OBLIGATIONS AT PT. GEO INDOGREEN WORKS: EVALUASI PAJAK PERTAMBAHAN NILAI TERHADAP PEMENUHAN KEWAJIBAN PERPAJAKAN PADA PT. GEO INDOGREEN KARYA - Dewi Indah Sari; Yanti Budiasih (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2021)
In general, this research aims to find out whether the Implementation of Value Added Tax has been done correctly. This research aims to find out if PT. Geo Indogreen Karya has provided value added tax implementation services in increasing tax revenues at the tax service office optimally (based on value added tax procedures in accordance with applicable laws), and what efforts have been made by PT. Geo Indogreen Karya to overcome the obstacles that arise during the process of implementing the value added tax. The data used is sourced from the primary data of PT. Geo Indogreen Karya. The research methodology used by the authors is with qualitative analysis techniques. Especially for quantitative data analysis techniques, the author analyzes the data that has been obtained to get a broader meaning by calculating and interpreting the data that has been evaluated is associated with existing theories. The conclusion that can be drawn, that PT. Geo Indogreen Karya has carried out the implementation of VAT procedures optimally. Tax examiners have conducted a series of activities to search, collect, process data and or other information to test compliance with the fulfillment of tax obligations and for other purposes in order to implement the provisions of tax laws and regulations. There are still many procedures for implementing VAT that do not understand how to increase tax revenue, so there are obstacles at the time of confirmation submission that will result in the inhibition of the examination process